2017
DOI: 10.1556/2006.6.2017.052
|View full text |Cite
|
Sign up to set email alerts
|

An investigation into problematic smartphone use: The role of narcissism, anxiety, and personality factors

Abstract: Background and aimsOver the last decade, worldwide smartphone usage has greatly increased. Alongside this growth, research on the influence of smartphones on human behavior has also increased. However, a growing number of studies have shown that excessive use of smartphones can lead to detrimental consequences in a minority of individuals. This study examines the psychological aspects of smartphone use particularly in relation to problematic use, narcissism, anxiety, and personality factors.MethodsA sample of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
118
1
6

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 189 publications
(145 citation statements)
references
References 64 publications
(88 reference statements)
11
118
1
6
Order By: Relevance
“…Hughes & Burke, 2018;Lapierre & Lewis, 2016;Li et al, 2015;Rotondi et al, 2017;Toda, Ezoe, Mure, & Takeshita, 2016), and mood or anxiety disorders (e.g. Alhassan et al, 2018;Arpaci, Baloğlu, Özteke Kozan, & Kesici, 2017;Elhai, Levine, Dvorak, & Hall, 2016, 2017Gao, Xiang, Zhang, Zhang, & Mei, 2017;Hussain, Griffiths, & Sheffield, 2017;Kim & Koh, 2018;Kim, Joo, Han, Kim, & Choi, 2018;Kim, Jang, Lee, Lee, & Kim, 2018). While some have interpreted this to indicate that smartphones are causing lower levels of well-being, it is important to consider that well-being and related dispositional factors may also cause perceived and actual problematic smartphone usage.…”
Section: Smartphone Usage and Well-beingmentioning
confidence: 99%
“…Hughes & Burke, 2018;Lapierre & Lewis, 2016;Li et al, 2015;Rotondi et al, 2017;Toda, Ezoe, Mure, & Takeshita, 2016), and mood or anxiety disorders (e.g. Alhassan et al, 2018;Arpaci, Baloğlu, Özteke Kozan, & Kesici, 2017;Elhai, Levine, Dvorak, & Hall, 2016, 2017Gao, Xiang, Zhang, Zhang, & Mei, 2017;Hussain, Griffiths, & Sheffield, 2017;Kim & Koh, 2018;Kim, Joo, Han, Kim, & Choi, 2018;Kim, Jang, Lee, Lee, & Kim, 2018). While some have interpreted this to indicate that smartphones are causing lower levels of well-being, it is important to consider that well-being and related dispositional factors may also cause perceived and actual problematic smartphone usage.…”
Section: Smartphone Usage and Well-beingmentioning
confidence: 99%
“…Self-regulation . Life satisfaction 2015a;Carbonell et al 2012;Hussain et al 2017;Lopez-Fernandez et al 2017). Several symptoms of problematic smartphone use have been identified including excessive reassurance behaviours (e.g.…”
mentioning
confidence: 99%
“…Although mobile phones, especially smartphones, offer benefits in terms of communication and access to information, there is growing evidence that they can have negative effects and that their use can become problematic among a small minority of individuals (e.g. Bianchi and Phillips 2005;Billieux et al 2015a;Carbonell et al 2012;Hussain et al 2017;Lopez-Fernandez et al 2017). Several symptoms of problematic smartphone use have been identified including excessive reassurance behaviours (e.g.…”
mentioning
confidence: 99%
“…However, as discussed by Billieux (2012), in a minority of cases, problematic mobile phone use can also have harmful consequences. Studies across a range of countries have identified that problematic, excessive or addictive mobile phone (or smartphone) use can have negative psychological consequences such as anxiety and/or low psychological wellbeing (Bianchi and Phillips 2005;Billieux et al 2015a;Ha et al 2008;Hussain et al 2017;Lepp et al 2014;Leung 2008). It appears that the more negative side of smartphone use could be a global problem and more studies are needed to understand when, where, and how access to smartphones may be harmful.…”
mentioning
confidence: 99%